Grenzregion Polen – Deutschland: gestärkt durch die COVID-19-Pandemie; Border Region Between Poland and Germany: Strengthened by the COVID-19 Pandemic - Steffen Fleßa; Julia Kuntosch (Wirtschaftsdienst, 2022)
Die COVID-19-Krise hatte erhebliche Auswirkungen auf die Grenzregion Polen - Deutschland. Der Beitrag untersucht, ob die Pandemie tatsächlich den Abstand zwischen der Grenzregion als strukturschwacher Region und dem Rest von Deutschland erhöhen wird, oder ob die Krise sogar eine Chance bietet. Hierzu wurden neben einer Online-Befragung ebenfalls Experteninterviews durchgeführt und ausgewertet. Die Zielregion ist vergleichsweise gut durch die Krise gekommen, jedoch sollte die Region die Chance nutzen und bereits begonnene Veränderungen wie Digitalisierung und Flexibilisierung weiter vorantreiben. – – The COVID-19 pandemic is a humanitarian tragedy with millions of deaths worldwide. However, this virus is also a tremendous economic challenge. There is some evidence that vulnerable groups and regions are in particular at risk of suffering from unemployment, insolvency and other economic hardships during the pandemic. We analyse the economic consequences on one of the poorest regions, the borderland between Germany and Poland. Based on statistical analysis, an online survey of entrepreneurs and key-informant interviews, we can conclude that the consequences of the pandemic are not as disastrous for the region as expected. The instruments of mitigating the economic challenges (including support for enterprises, unemployment insurance and support for temporary under-utilisation of "Kurzarbeitergeld") were quite successful. The survey partners even see some improvements, in particular in the field of digitalisation. All agree that the flow of information and cooperation between Poland and Germany should have been more intensive to reflect the manifold economic and personal interdependencies between the two countries.
Keywords: R10; R11; R12; 330; Grenzregion; Internationale Wirtschaftsbeziehungen; Coronavirus; Deutschland; Polen